Development of slide agglutination test for the rapid diagnosis of Mycoplasma infection in the chicken (Bangladesh Veterinarian, 2012)
Mycoplasma gallisepticum is considered to be the most important pathogenic Mycoplasma sp. and occurs world-wide. For effective control of mycoplasmosis, early diagnosis is the cornerstone, but the cultural method is laborious, expensive and timeconsuming, whereas agglutination test is easy to perform in field conditions and cheaper. Mycoplasma gallisepticum was isolated and two types of stained antigen produced. The antigen produced distinct tiny clumps with positive antisera of Mycoplasma spp. The slide agglutination system was sensitive, reliable and cheap. This method may be used to screen Mycoplasma infections in poultry farms.DOI: http://dx.doi.org/10.3329/bvet.v28i2.10688Bangl. vet. 2011. Vol. 28, No. 2, 80 84